Reflective practices for future journalism - Ramaker, Timon (Javnost (Ljubljana), 2015)
In newsrooms journalists encounter numerous constraints accelerated by increasing technological and economic pressures. The complexity of the job and the need for (constant) innovation coupled with the rising call for transparency and accountability ask for journalists who "reflect-in-action". Newsroom ethnographies consistently suggest that journalists experience a gap between the wish for increased self-reflection and its actual practice. Additionally, both newsroom research and journalists' expressions in the trade press show significant resistance against reflection as being a largely academic exercise, or simply too time-consuming. We propose that considering reflection primarily from a learning perspective can overcome this resistance. Secondly, the article acknowledges that in order to enable professionals to fit reflection into their precarious practice, critical reflection should develop out of the practice itself. Reflection only makes sense if it starts from the sense of immediacy and autonomy within journalistic practice, recognises the constraints that journalists face and acknowledges the aversion among journalists against standardised protocols in their craft. Outlining the basic tenets of reflective practice, journalism's current precarity and the learning perspective, we propose further research in how informal reflective practices can enhance professional autonomy.
Keywords: Ethics; Etika; Informal education; Journalism; Neformalno učenje; Novinarstvo; Refleksija; Reflexion